Scanning Electrochemical Microscopy as a Tool for the Characterization of Dental Erosion - Pollyana S. Castro; Alex S. Lima; Tiago L. Ferreira; Mauro Bertotti (International Journal of Electrochemistry, 2011)
When the tooth is exposed to acidic environments, an irreversible loss of dental hard tissue occurs in a process called dental erosion. In this work, the scanning electrochemical microscopy (SECM) was used to probe the consumption of protons at the vicinity of a tooth surface with a platinum microelectrode fixed at −0.5 (V) versus Ag/AgCl/KCl(sat). SECM approach curves were recorded to assess the extent of diffusion in the solution close to the tooth substrate. SECM images clearly demonstrated that the acid erosion process is very fast at solution pH values in the range between 3 and 4.